Representasi Perpustakaan dalam Film Nasional (Analisis Semiotika Roland Barthes) - Ibrahim, Andi; K, Ratna; Tahir, Arsil (Inkunabula: Journal of Library Science and Islamic Information, 2023)
This research focuses on the representation of libraries in national films. The primary objective of this study is to analyze how libraries are portrayed in films using a semiotic analysis approach, primarily drawing from Roland Barthes’ theory. The research methodology employed is qualitative descriptive with a semiotic analysis approach based on Roland Barthes’ theory. The findings of this research reveal various representations of libraries in several national films featuring library scenes and librarians. Some of the national films examined include "Ada Apa Dengan Cinta," "Adriana," "Refrain," "Pupus," "The Tarix Jabrix 2," "Marmut Merah Jambu," and "Kukira Kau Rumah." Through the analysis, these national films depict different conditions of libraries, both in school and university settings, and diverse representations of librarians, ranging from young to middle-aged professionals. In the context of these films, libraries are illustrated as favored gathering spots for students and university attendees during their breaks. Furthermore, the librarians in these films are portrayed as ideal service providers, even though some of the systems they utilize remain conventional. Consequently, this research offers valuable insights into how libraries and librarians are represented in national cinema and how perceptions of library institutions and individual librarians are reflected in these cinematic works. Abstrak Penelitian ini berfokus pada representasi perpustakaan dalam film nasional. Tujuan utama penelitian ini adalah menganalisis bagaimana perpustakaan direpresentasikan dalam film menggunakan pendekatan analisis semiotika, terutama teori Roland Barthes. Metodologi penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan analisis semiotika teori Roland Barthes. Hasil penelitian ini mengungkapkan berbagai representasi perpustakaan dalam beberapa film nasional yang menampilkan adegan perpustakaan dan pustakawan. Beberapa film nasional yang dijadikan sampel dalam penelitian ini meliputi "Ada Apa Dengan Cinta," "Adriana," "Refrain," "Pupus," "The Tarix Jabrix 2," "Marmut Merah Jambu," dan "Kukira Kau Rumah." Melalui analisis, film-film nasional ini menggambarkan berbagai kondisi perpustakaan, baik di sekolah maupun kampus, serta berbagai representasi pustakawan, baik yang masih muda maupun yang sudah berusia separuh baya. Dalam konteks film ini, perpustakaan diilustrasikan sebagai tempat favorit siswa dan mahasiswa untuk berkumpul selama waktu istirahat. Selain itu, pustakawan dalam film ini dijelaskan sebagai pemberi layanan yang ideal, meskipun sebagian besar sistem yang digunakan masih bersifat konvensional. Dengan demikian, penelitian ini memberikan wawasan penting tentang bagaimana perpustakaan dan pustakawan direpresentasikan dalam film nasional, serta bagaimana persepsi terhadap institusi perpustakaan dan individu pustakawan tercermin dalam karya-karya sinematik ini.